2015
DOI: 10.1111/josh.12228
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of School‐Initiated Physical Activity Program on Secondary School Students' Physical Activity Participation

Abstract: Gråstén, Arto Students' physical activity, physical education enjoyment, and motivational determinants through a three-year school-initiated program Jyväskylä: University of Jyväskylä, 2014, 12 p. (+ included articles) (Studies in Sport, Physical Education, and Health ISSN 0356-1070; 205) ISBN 978-951-39-5713-1 (nid.) ISBN 978-951-39-5714-8 (PDF) Finnish abstract Diss.Patterns of physical activity in adulthood are often established during adolescence, making this an important period for promoting physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 125 publications
1
29
0
Order By: Relevance
“…More specifically, school‐based obesity preventions provide a particularly practical approach, as children spend most waking hours in school and can be engaged in before‐ and after‐school activities designed to fill the time when parents may be working . Although school‐based interventions that focus on high weight groups (secondary prevention/intervention) show modest improvements in reducing overweight in children, those that have not specifically targeted overweight children (primary prevention) have shown mixed results . Because programs involving physical activity and nutrition education together have shown more promising results than either aspect alone, the majority of recent school‐based obesity interventions have adopted this approach …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, school‐based obesity preventions provide a particularly practical approach, as children spend most waking hours in school and can be engaged in before‐ and after‐school activities designed to fill the time when parents may be working . Although school‐based interventions that focus on high weight groups (secondary prevention/intervention) show modest improvements in reducing overweight in children, those that have not specifically targeted overweight children (primary prevention) have shown mixed results . Because programs involving physical activity and nutrition education together have shown more promising results than either aspect alone, the majority of recent school‐based obesity interventions have adopted this approach …”
mentioning
confidence: 99%
“…16 Although school-based interventions that focus on high weight groups (secondary prevention/intervention) show modest improvements in reducing overweight in children, [17][18][19] those that have not specifically targeted overweight children (primary prevention) have shown mixed results. 18,[20][21][22] Because programs involving physical activity and nutrition education together have shown more promising results than either aspect alone, the majority of recent school-based obesity interventions have adopted this approach. 23,24 Despite surface similarities in curricula, many school-based interventions in the United States have shown discrepant findings.…”
mentioning
confidence: 99%
“…The results showed that the program was ineffective in enhancing children's total MVPA across 2 years. This was not expected, since the particular program was effective in increasing middle school students' MVPA across 1 school year . Several previous school‐based interventions have also been effective in promoting students' MVPA .…”
Section: Discussionmentioning
confidence: 90%
“…Based on Ames, 2 types of motivational climate are suggested to exist: a task‐involving climate (psychological climate that supports self‐referenced learning and effort) and an ego‐involving climate (supports normative evaluation, such as competition and defeating others) . Previous studies have revealed that task‐involving climate in school PE correlated with increased MVPA engagement and PE enjoyment, whereas an ego‐involving climate in PE has shown either to uncorrelate with PE enjoyment and MVPA or correlate with low levels of enjoyment . The recent meta‐analysis examining the effectiveness of motivational climate interventions in PE showed task‐involving interventions to have small to moderate effects in enhancing school students' affective (enjoyment), behavioral (MVPA), and cognitive (knowledge) outcomes .…”
mentioning
confidence: 93%
“…[15][16][17] In contrast, ego-involving climate in PE has shown either a neglible correlation 13 or negative correlation with physical competence. 15 Previous intervention studies in PE contexts demonstrated that students' perceived competence towards physical activity increased when emphasizing task-involving teaching practices.…”
mentioning
confidence: 99%